Internal Supervision Model Using Professional Learning Community for Secondary Schools (International Journal of Psychosocial Rehabilitation, 2020)
This research aimed to develop internal supervision model using professional learning community for secondary schools and to study results of application of the internal supervision model using professional learning community for secondary schools. There were 2 phases, namely, the design and evaluation of internal supervision model using professional learning community for secondary schools, and the study of application of the internal supervision model using professional learning community for secondary schools. The findings revealed that the internal supervision model using professional learning community for secondary schools consisted of 5 stages as following: Stage 1 Preparing (P); Stage 2 Planning (P); Stage 3 Implementing (I); Stage 4 Reflecting, Improving and Evaluating (R); and Stage 5 Concluding and Reporting (C). The procedure of PLC comprises 6 components, which are 1) Shared Vision; 2) Collaborative Teamwork; 3) Shared Leadership; 4) Professional Learning and Development; 5) Caring Community; and 6) Supportive Structure, in which all 9 experts considered that it is theoretically reasonable and the feasibility is generally at a high level. The effects of applying the internal supervision model using professional learning community for secondary schools indicated that the evaluation after the development of Deputy Directors of Academic Affairs and Heads of Department on internal supervision and professional learning community was higher than before. In addition, the evaluation after the development of Deputy Directors of Academic Affairs and Heads of Department on implementation based on the internal supervision and professional learning community was higher than before, in overall. Furthermore, satisfaction of Deputy Directors of Academic Affairs and Heads of Department towards the internal supervision model using professional learning community for secondary schools was generally at a high level.